A organização da escolaridade em ciclos de aprendizagem : uma análise dos processos de recontextualização e de formulação de políticas - Stremel, Silvana (2011)
This work presents an analysis of the process whereby the policy called as Cycles of Learning (a kind of non-retention policy for Primary Education) was recontextualised and formulated in Brazil. The aims of the research can be described as follows: a) to analyse how the Cycles of Learning policy has been recontextualised and justified in Brazilian state schools that have adopted it; b) to explain historical aspects as well as the bases of the policy known as Cycles of Learning; and c) to analyse to what extent the proposals of the Cycles of Learning are related to the building of a truly inclusive and democratic education system. The theoretical basis of the research includes: contributions from Bernstein (1996, 1998) on the concept of recontextualisation of the pedagogical discourse; authors who provide the basis for the role of school and the building of an inclusive and democratic education system (APPLE, 2001; BELLONI, 2003; CAMINI, 2001; YOUNG, 2007); and authors who discuss the policy of cycles (BARRETTO; MITRULIS, 1999; BARRETTO; SOUSA, 2005; FREITAS, 2003; MAINARDES, 2007, 2009; PERRENOUD, 2004). The research consisted of the analysis of official documents from seven teaching networks (municipal education systems) that have adopted the Learning Cycles method (Curitiba-PR, Ponta Grossa-PR, Recife-PE, Salvador- BA, São Luís-MA, Telêmaco Borba-PR and Vitória da Conquista-BA). The results indicate that: a) teaching networks have been recontextualising the Cycles of Learning policy according to local contexts, political and ideological contexts, concepts and experiences from cycles of other networks etc.; b) in all networks studied the implementation of Cycles of learning aimed to provide an inclusive and democratic education system; c) the implementation of the Cycles of Learning resulted in a process whereby curriculum was restructured, and the networks analysed opted for a common curriculum; d) in general the investigated proposals were formulated without any participation or involvement of teachers and other education professionals. Furthermore, it was concluded that the analysis of initial documents of the referred networks provides elements for understanding the concept of cycle that was adopted and the general guidelines for its implementation. Nevertheless, it should be noted that in practice such guidelines are modified, reinterpreted, and recontextualised. Although the research aimed to provide a deeper look into aspects related to the origin,characteristics and bases of the Cycles of Learning, it led to the conclusion that there are still aspects in need of further investigations, namely: the bases of the Cycles of Learning policy,the variety of options and decisions taken by teaching networks to shape the policy of cycles, the impact of such cycles in the changes of pedagogical practices and in the students’ performance, and the curriculum implications of implementing schooling organised in Cycles of Learning.